Using writing to learn across the content areas - Association for Supervision and Curriculum Development (Virginia : Association for Supervision and Curriculum Development, 2005)
This cd-rom provides writing tool activities for pre-writing, during writing and postwriting
An ASDC action tool
Keywords: Language arts -- Correlation with content subjects; English language -- Composition and exercises -- Study and teaching